Comparative evaluation of the energy and economic efficiency of vapor compression heat pumps in modernization of large chemical and oil refining industries. Part 1 - V. L. Yusha; M. A. Sutyaginskiy; Yu. A. Potapov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The question of the feasibility of increasing the energy efficiency of large chemical and oil refining industries by replacing furnace heaters of process heat carriers and raw materials with vapor compression heat pumps is considered. An analysis of the relationship between the technical configuration of vaporcompression heat pumps, the operating parameters of their operation (determining the value of the energy conversion coefficient) and the ratio of the cost of various energy carriers is carried out. The presented results of a comparative analysis of the energy efficiency of various options for replacing a furnace with a vapor compression heat pump reflect the decisive influence of the technical level and design configuration of a vapor compression heat pump on the choice of the preferred upgrade option. However, a significant difference in commercial energy prices significantly changes the preferred ranking of these options.